(untitled) (Серія: Історія. Політологія, 2021)
У статті розглядаються питання політичної приналежності Покуття – спірної території між Польщею та Молдавією наприкінці XV– на початку XVІ ст. У роки правління Стефана ІІІ (1457–1504) та Богдана ІІІ (1504–1517) ці території, в тому числі й Буковини, стають ареною протистояння могутніх держав – Османської імперії, Польщі, Угорщини та Молдавії, а також запеклих польсько-молдавських збройних сутичок у 1506-1510 рр. Для Польщі молдавські землі були своєрідною буферною зоною від турків, для Туреччини – представляли значний інтерес через свої оборонні споруди, а саме Сучавську та Хотинську фортеці. The struggle for Pokuttya between Poland and Moldova has been going on with varying degrees of success for four decades. It all started during the reign of the Moldavian voivode Stephen III. In 1491 he marched on Pokuttya, trying to annex it to his state. He managed to do it. However, only for a while. The next attempt to return the Penance was made by Stephen the Great ten years later, in 1502. She was successful. However, on July 2, 1504, the voivode died. The son of Stephen III Bogdan, later nicknamed the Blind, became the ruler of Moldavia. And already in 1505 he returned Pokuttya to Poland. His goal was to marry the sister of King Alexander I of Poland, Elizabeth Jagiellonian. In 1506 Alexander Jagiellonian died. The king was his younger brother Sigismund I the Elder, who abandoned the planned alliance. This has led to a sharp deterioration in relations with Moldova. Therefore, in August 1506 Pokuttya was captured by the troops of Bohdan III. The Polish army under the command of S. Khodetsky and M. Kamenetsky drove the Moldavians out of Pokuttya, and later defeated their army near Chernivtsi. Taking advantage of the participation of King Sigismund I’s troops in the Second Lithuanian-Moscow War, on June 29, 1509, Bohdan III began a campaign in Pokuttya, Podillya and the Ruthenian Voivodeship. In particular, the Moldovan army laid siege to Kamyanets, Halych, Lviv and Rohatyn. However, the campaign ended in failure. None of these cities was taken. The answer was not long in coming. The Polish army under the leadership of the Grand Crown Hetman M. Kamenetsky devastated several Moldavian cities across the Dniester. On their way out, near Khotyn, on October 4, the Poles were attacked by the Moldavian army, but the long battle did not reveal a winner. Therefore, on January 23, 1510, a peace treaty was signed. As a result of the signing of the Polish-Moldavian peace treaty of 1510, the war between Poland and Moldavia was ended, conflicts were settled, and hospodar Bogdan III received Poland and Hungary as allies. However, Pokuttya remained part of Poland.